Direct Laser Writing on Graphene with Unprecedented Efficiency of Covalent Two-Dimensional Functionalization - Wei, Tao; Al-Fogra, Sabrin; Hauke, Frank; Hirsch, Andreas (Journal of the American Chemical Society, 2020)
Laser writing as a simple and straightforward method for covalent 2D patterning of graphene remains challenging. Here, we report a facile and efficient approach for a laser-induced 2D patterning of graphene utilizing silver trifluoroacetate, providing an unprecedented high degree of functionalization. The use of laser-triggered photolysis of silver trifluoroacetate to generate trifluoromethyl radicals, confined only to the laser-irradiated region, leads to the selective reaction of graphene, thereby completing direct laser writing on graphene toward a spatially resolved 2D-patterned architecture. This highly 2D-functionalized graphene is completely reversible. Furthermore, a more complex patterned graphene hybrid architecture was constructed, taking advantage of the simultaneously produced/patterned silver nanoparticles during the laser-writing process. Considering the simplicity of this approach and its ability to provide high degrees of functionalization, the prerequisite of 2D patterning of other 2D materials based on this method is provided.
CRIS-Team Scopus Importer:2021-01-15